PERKEMBANGAN KEABSAHAN PERKAWINAN BEDA AGAMA DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN - Arfansyah Munthe; Rosnidar Sembiring; Edy Ikhsan; Idha Aprilyana Sembiring (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: This research is based on the fact that interfaith marriages are not strictly regulated in Law No. 1 of 1974 concerning Marriage. This results in a legal vacuum. With the phenomenon of interfaith marriages in Indonesia, the government accommodates interfaith marriages through Law Number 23 of 2006 concerning Population Administration as a solution to fill this legal vacuum. Article 35 letter a states that marriage registration also applies to marriages determined by the court, namely marriages between people of different religions. This type of normative juridical research is supported by the results of interviews with sources, the research approach uses a statutory approach and a case approach to interfaith marriages which have become court decisions and have permanent legal force. The results of this research show that from an Islamic religious perspective, interfaith marriages are absolutely and absolutely prohibited, from a Christian religious perspective, interfaith marriages are prohibited in its teachings. From the Catholic perspective, interfaith marriages are an obstacle, interfaith marriages are possible with a dispensation, whereas in Buddhism there is no prohibition on interfaith marriages. Keywords: Development, Validity, Interfaith Marriage Abstrak: Penelitian ini di latar belakangi dengan tidak diaturnya perkawinan beda agama secara tegas dalam Undang-Undang No 1 tahun 1974 Tentang Perkawinan. Sehingga mengakibatkan adanya kekosongan hukum. Dengan adanya fenomena perkawinan beda agama di Indonesia pemerintah mengakomodir perkawinan beda agama melalui Undang-Undang Nomor 23 tahun 2006 tentang Administrasi Kependudukan sebagai solusi untuk mengisi kekosongan hukum tersebut. Dalam pasal 35 huruf a menyebutkan bahwa pencatatan perkawinan berlaku pula bagi perkawinan yang ditetapkan oleh pengadilan adalah perkawinan yang dilakukan antar umat yang berbeda agama. Jenis penelitian yuridis normatif dengan di dukung hasil wawancara dengan narasumber, pendekatan penelitian menggunakan pendekatan perundang-undangan dan pedekatan kasus terhadap perkawinan beda agama yang telah menjadi penetapan pengadilan dan telah berkekuatan hukum tetap. Hasil dari penelitian ini menunjukkan bahwa dalam perpektif agama Islam perkawinan beda agama dilarang dan mutlak, perpektif agama Kristen perkawinan beda agama dilarang dalam ajaranya. Perpektif agama Katolik perkawinan beda agama adalah suatu halangan, perkawinan beda agama dimungkinkan dengan adanya dispensasi, sedangkan dalam agama Buddha tidak ada larangan mengenai perkawinan beda agama. Kata kunci: Perkembangan, Keabsahan, Perkawinan Beda Agama